The impacts of financial regulations: solvency and liquidity in the post-crisis period. Issue 3 (10th July 2017) - Baker, Colleen; Cummings, Christine; Jagtiani, Julapa
Abstract : Purpose: Basel III and the capital stress testing introduced new requirements and new definitions while retaining the structure of the pre-2010 requirements. The total number of requirements increased, making it difficult to determine which and how many constraints are binding. The purpose of this paper is to discuss the new financial regulations in the post-financial crisis period, focusing on the capital and liquidity regulations. Design/methodology/approach: The authors explore the impact of financial regulations using various data sources – financial and accounting data from Y-9C Reports. Market data such as daily bond trading from TRACE through the Wharton Data Research Services and Treasury yield from the Bloomberg. The authors use regression analysis to examine the roles of capital adequacy and liquidity regulations. Findings: The authors' analysis in this paper suggest that Basel III, CET1 and Level 1 HQLAs requirements post-financial crisis have reshaped the balance sheets of large financial institutions, with some differential impacts on traditional versus capital markets banks. These changes appear to respond to the binding constraints (CET1 being a preponderance of required regulatory capital, Level 1 HQLAs a majority of required HQLAs and the expense of both) created by these new requirements, which also appear to have constrained asset growth at such institutions. Consistent with the authors' view, their results suggest that the new requirements are less constraining for large traditional banks (such institutions show a rapid increase in CET1 capital to steady-state levels by 2012 and strong retail deposit rebuilding resulting in a relatively low required HQLA) and much more so, particularly the liquidity requirement, for the capital markets banks (such institutions show continuous building of CET1 capital over the post-crisis observation period, declines in the share of trading assets and increases in the share of HQLAs combined with efforts to increase retail deposits). Credit risk spreads rose dramatically during the financial crisis of 2008-2009. Although decreased, they remain higher and with greater dispersion (for both groups of banks) than pre-crisis. Preliminary regression analysis suggests that the market responds to changes in measured liquidity, rather than the regulatory capital ratios, when pricing bank risk (as reflected on bond spreads). Research limitations/implications: The estimation is based on historical relationship in the data. We must be cautious in extrapolating the results in a different environment. Practical implications: There appears to be an arbitrage between HQLA and retail deposits. Capital markets banks and traditional banks follow different business models as evident in the analysis in this paper. Social implications: Market pricing suggests that the liquidity measures are more transparent and easier to understand. Capital ratios are not as easy to interpret. Originality/value: Original research. To the authors' knowledge, there is no paper that examines impacts of capital and liquidity regulations after the crisis at capital markets banks vs traditional banks – using both accounting data and market data.